IDEAL REGULATIONS IN FULFILLING CHILDREN'S SUPPORT POST PARENTS' DIVORCE IN INDONESIA - M. Alpi Syahrin; Akbar izan; Jumni Nelli (EKSEKUSI, 2023)
AbstractProblems regarding the maintenance of children after the divorce of parents are always a problem, because many children's rights are neglected by parents, so they are not taken care of, especially matters relating to children's basic rights, namely the need for food, shelter, education and other facilities. other supporting facilities. Even though the two parents are no longer united in a marriage bond, the problem of fulfilling the maintenance of children is the responsibility of the parents and this should not be delegated to other people. After the divorce of the parents, therefore, it is necessary to discuss the importance of regulation in fulfilling the maintenance of children after the divorce of parents in Indonesia.Keywords: Regulations, Child Feed, IndonesiaAbstrakPermasalahan tentang nafkah terhadap anak setelah perceraian orang tua selalu menjadi masalah, karena banyak hak anak yang diabaikan oleh orang tua, sehingga tidak terurus, terutama adalah hal-hal yang berkaitan dengan hak dasar anak, yaitu Kebutuhan Pangan, tempat tinggal, pendidikan dan fasilitas-fasilitas penunjang lainnya. Walaupun Kedua orangtua tidak bersatu lagi dalam satu ikatan Perkawinan, namun Permaslahan pemenuhan nafkah terhadap anak merupakan tanggung jawab orangtua dan hal ini tidak boleh dilimpahkan kepada orang lain. Pasca perceraian orang tua, oleh Karena itu, maka perlu dibahas tentang pentingnya Regulasi dalam pemenuhan nafkah anak pasca perceraian orang tua di Indonesia.Kata kunci: Regulasi, Nafkah Anak, Indonesia